Comparison of Expectant and Excisional/Ablative Management of Cervical Intraepithelial Neoplasia Grade 2 (CIN2) in the Era of HPV Testing - Kevin Dominique Tjandraprawira; Adeola Olaitan; Aviva Petrie; Nafisa Wilkinson; Adam N. Rosenthal (Obstetrics and Gynecology International)
Objective. To investigate conservative and excisional/ablative treatment outcomes for cervical intraepithelial neoplasia grade 2 (CIN2) following introduction of virological test of cure. Methods. This was a retrospective study of prospectively collected data at a teaching hospital colposcopy unit. 331 sequential biopsy-proved CIN2 cases were involved. CIN2 cases diagnosed between 01/07/2014 and 31/12/2017 were either conservatively managed or treated with excision/ablation and then were followed up until discharge from colposcopy clinic and then using the national cervical cytology database. Outcomes were defined: cytological/histological regression was absence of high-grade CIN on biopsy and/or high-grade dysplasia; virological regression was cytological/histological regression and negative human papillomavirus testing; persistence was biopsy-proven CIN2 and/or moderate dyskaryosis; progression was biopsy-proven CIN3+ and/or severe dyskaryosis. Results. Median follow-up was 22.6 months (range: 1.9–65.1 months). Among 175 (52.9%) patients initially managed conservatively, 77.3% (133/172) regressed, 13.4% (23/172) persisted, 9.3% (16/172) progressed to CIN3+, and 97 (56.4%) patients achieved virological regression. 156 (47.1%) patients underwent initial excision/ablation, with an 89.4% (110/123) virological cure rate. After discharge, 7 (4.0%) and 3 (1.9%) patients redeveloped CIN in the conservative and treatment groups, respectively, during a median period of 17.2 months. Conclusion. Conservative management is a reasonable and effective management strategy in appropriately selected women with CIN2. High rates of histological and virological regression should be expected. The previously mentioned data provide useful information for deciding management options.